ACCURACY OF ULTRASOUND COMPARED TO CLINICAL ESTIMATE OF ESTIMATED FETAL WEIGHT - Yasmeen, Almas; Aslam, Rakhshanda; Tayyab, Fareeha; Malik, Laraib; Afroze, Sadaf; Tabasam, Shakara (Journal of Postgraduate Medical Institute, 2023)
Objective: To evaluate accuracy of ultrasonography with clinical examination in assessing fetal weight with birth weight in actual considering as the gold standard. Methodology: From January to July 2022, the Department of Obstetrics and Gynaecology at Pak Emirates Military Hospital, Rawalpindi, conducted a study comparing Leopold's procedures and ultrasonic review for estimating fetal weight. Actual birth weight served as the gold standard. Data was collected from women starting at 34 weeks of gestational age. Neonatal outcomes and maternal demographic data were noted. Comparison metrics included overall absolute error, overall absolute percent error, and percent errors greater than 10% and 20%. Results highlighted the accuracy of both methods in estimating fetal weight. Results: A total of 377 pregnant women with singleton term pregnancies were recruited for study with average gestational age 3of 8+4 weeks gestation including 65.7% primiparous women, 34.3% women were obese and 11.3% had gestational diabetes with 2.9% huge for gestational age infants. Statistical analysis revealed that a significant difference was noted for estimation of weights in favor of ultrasonic measures for all error estimation groups. Conclusion: Ultrasound has significantly better accuracy in estimation of fetal weight as compared to clinical examination in pregnant women.